Effects of Empagliflozin in Women and Men With Heart Failure and Preserved Ejection Fraction. Issue 14 (13th September 2022) - Butler, Javed; Filippatos, Gerasimos; Siddiqi, Tariq Jamal; Ferreira, João Pedro; Brueckmann, Martina; Bocchi, Edimar; Böhm, Michael; Chopra, Vijay K.; Giannetti, Nadia; Iwata, Tomoko; Januzzi, James L.; Kaul, Sanjay; et al.
Abstract : Background: Women and men with heart failure (HF) and preserved ejection fraction may differ in their clinical characteristics and their response to therapy. The aim of this study was to evaluate the influence of sex on the effects of empagliflozin in patients with HF and preserved ejection fraction enrolled in the EMPEROR-Preserved trial (Empagliflozin Outcome Trial in Patients With Chronic Heart Failure With Preserved Ejection Fraction). Methods: The effects of empagliflozin on the primary outcome of cardiovascular death or hospitalization for HF and on secondary outcomes (including total HF hospitalization, cardiovascular and all-cause mortality, and Kansas City Cardiomyopathy Questionnaire scores) were compared in women and men in the overall cohort and in subgroups defined by left ventricular ejection fraction (41%–49%, 50%–59%, and ≥60%). The effects of empagliflozin on physiological measures, including changes in systolic blood pressure, uric acid, hemoglobin, body weight, and natriuretic peptide levels, were also assessed. Results: Of the 5988 patients randomized, 2676 (44.7%) were women. In the placebo arm, women tended to have lower risk for adverse outcomes, including a lower risk of all-cause mortality (hazard ratio, 0.69 [95% CI, 0.56, 0.84]). Compared with placebo, empagliflozin reduced the risk of cardiovascular death or hospitalization for HF to a similar degree in both sexes (hazard ratio, 0.81 [95% CI, 0.69, 0.96] for men; and hazard ratio, 0.75 [95% CI, 0.61, 0.92] for women; P interaction =0.54). Sex did not modify the relationship between empagliflozin and outcomes across ejection fraction groups. Similar results were seen for secondary outcomes and physiological measures. Compared with placebo, empagliflozin improved the Kansas City Cardiomyopathy Questionnaire Clinical Summary Score to a similar extent in both sexes (1.38 for men versus 1.63 for women at 52 weeks; P interaction =0.77); the results were similar for Kansas City Cardiomyopathy Questionnaire overall summary score and total summary score. Conclusions: Empagliflozin produced similar benefits on outcomes and health status in women and men with HF and preserved ejection fraction. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03057951.